Conflict of the bambas in Peru: Frame Analysis of ethnocentrism (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
The article contributes to the reflection on the Las Bambas conflict in Peru, the objective was to analyze the logic that makes the media prioritize certain issues in the construction and dissemination of their discourses regarding the Las Bambas conflict and in this process to question the invisibility of the underlying problems linked to the conflict. Thus, on the one hand, based on framing analysis to identify what the most-watched television media in Peru prioritize, and on the other hand, ethnocentrism as a theoretical approach to reflection the logic behind such prioritization of contents, the essay analyzes the framing of the Las Bambas conflict from the media. This shows that behind the hierarchization of the actors in the conflict and their roles; the invisibilization of others and their demands and what the media do not say about the conflict, issues related to environmental protection, exist an ethnocentric logic based on hegemonic categories expressed in simplifi cations and generalizations that are legitimized because they represent the beliefs of Peruvian society about the rural communities. Finally, these findings demonstrate that media discourses can validate and reproduce power structures that place the population affected by mining activities at a disadvantage.
Keywords: Discourses; ethnocentrism; framing; conflict; simplification